A New NLRP3 Inflammasome Inhibitor, Dioscin, Promotes Osteogenesis. Issue 1 (9th December 2019) - Yin, Wei; Liu, Shuo; Dong, Ming; Liu, Qicheng; Shi, Chun; Bai, Hua; Wang, Qian; Yang, Xue; Niu, Weidong; Wang, Lina
Abstract: Refractory periapical periodontitis, which is a persistent infection after root canal treatment, still has no effective treatment. Its most common pathogen is Enterococcus faecalis . Here, the precursor of phytosteroids, dioscin, is introduced to fight against the inflammation induced by Enterococcus faecalis . The findings suggest that dioscin inhibits the nuclear transport of NF‐κB and the expression of reactive oxygen species (ROS) induced by lipoteichoic acid from the Enterococcus faecalis . The decrease in mRNA and protein levels of NLRP3, Caspase‐1, and IL‐1β is observed in dioscin treated mouse macrophages. In the MC3T3‐E1 cells, dioscin also promotes the expression of osteogenic‐related factors, ALP, Runx2, and OCN. The increased formation of mineralized nodules after the application of dioscin further indicates that dioscin has the potential to promote osteogenesis. The above results suggest dioscin can be a potential root canal irrigation or root canal sealant for the treatment of refractory apical periodontitis. Abstract : Dioscin, an anti‐oxidative stress drug, significantly inhibits the activity of NLRP3 inflammasomes induced by lipoteichoic acid from the Enterococcus faecalis . It also promotes the expression of osteogenic related factors, ALP, Runx2, and OCN, and the formation of mineralized nodules.